A tomato B‐box protein SlBBX20 modulates carotenoid biosynthesis by directly activating PHYTOENE SYNTHASE 1, and is targeted for 26S proteasome‐mediated degradation. Issue 1 (13th August 2018) - Xiong, Cheng; Luo, Dan; Lin, Aihua; Zhang, Chunli; Shan, Libo; He, Ping; Li, Bo; Zhang, Qiaomei; Hua, Bin; Yuan, Zilv; Li, Hanxia; Zhang, Junhong; et al.
Summary: Carotenoids play important roles in many biological processes, such as light harvesting, photoprotection and visual attraction in plants. However, the regulation of carotenoid biosynthesis is still not fully understood. Here, we demonstrate that Sl BBX20, a B‐box (BBX) zinc‐finger transcription factor, is a positive regulator of carotenoid accumulation in tomato ( Solanum lycopersicum ). Overexpression of SlBBX20 leads to dark green fruits and leaves and higher levels of carotenoids relative to the wild‐type. Interactions between Sl BBX20 and DE‐ETIOLATED 1 ( Sl DET1) lead to the ubiquitination and 26S proteasome‐mediated degradation of Sl BBX20. Moreover, deficiencies in the components of the CUL4‐DDB1‐DET1 complex enhanced the stability of the Sl BBX20 protein. Thus, we conclude that Sl BBX20 is a substrate of the CUL4‐DDB1‐DET1 E3 ligase. Sl BBX20 can activate the expression of PHYTOENE SYNTHASE 1, encoding a key enzyme in carotenoid biosynthesis, by directly binding to a G‐box motif in its promoter, which results in the elevated levels of carotenoids in SlBBX20 overexpression lines. We identified a key regulator of carotenoid biosynthesis and demonstrated that the stability of Sl BBX20 is regulated by ubiquitination. These findings provide us a new target for the genetic improvement of the nutritional quality of tomato fruit.